Undoing Suicidism: A Trans, Queer, Crip Approach to Rethinking (Assisted) Suicide by Alexandre Baril - Dankwort, Juergen (Canadian Journal of Bioethics / Revue canadienne de bioéthique)

(untitled) (Programmes de bioéthique, École de santé publique de l'Université de Montréal, 2026)
There is no more compelling a current issue than critically examining the topics of suicide prevention and assisted suicide. That has been exceptionally accomplished by Alexandre Baril in his book Undoing Suicidism: A Trans, Queer, Crip Approach to Rethinking (Assisted) Suicide (2023). While it is unquestionably a major contribution to the field of suicide prevention and assisted dying, remarkably explored in a single book, the author’s thorough and critical reasoning appears to fall short where he explores existing and evolving voluntary assisted suicide approaches in the second part of his revolutionary work.